Penerapan Metode Lean Warehousing dalam Analisis Pemborosan pada Proses Aliran Pergudangan - Putra, Wiedy Irawan; Widjajati, Endang Pudji (Universitas Batanghari Jambi, 2025)
PT. XYZ is one of the leading manufacturers of ceramic tiles for walls and floors. The application of the lean warehousing method is carried out using Value Stream Mapping to map each flow of the process that occurs in warehousing activities. Determining the weight of each waste that occurs using the Waste Assessment Model (WAM) method. The results of the study show the order of waste or waste from the highest to the lowest percentage, namely defects are 20.15%, overproduction is 17.44%, unnecessary motion is 16.86%, unnecessary inventory is 16.78%, transportation is 11.55%, waiting is 11.33% and unappropriate processing is 5.88%. The three types of waste with the highest frequency of values in the warehousing flow process are waste defects with a value of 20.15%, waste overproduction with a value of 17.44%, and waste unnecessary motion with a value of 16.86%, unnecessary inventory 16.78%. The results of the activity simplification obtained a total number of activities which previously amounted to 30 activities to 24 activities with an initial lead time of 19428 seconds and a lead time after improvement of 14100 seconds, so there is a time efficiency of 5328 seconds from the previous time.